2022
DOI: 10.1002/pc.26924
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of alkali and silane treatment on mechanical, flammability, and thermal degradation of hemp fiber/epoxy composite

Abstract: Currently, natural fiber composites are used in many applications (industrial, automotive, and construction) where fire resistance is a critical factor. The main objective of this research work is to investigate the thermal degradation and fire performance of raw and treated fiber composites developed using hand layup with different fiber loadings of 5, 10, 15, and 20 wt%. Alkali treatment (5%, wt/vol) and silane treatment (5%, wt/vol) were used to improve the thermal stability and compatibility of hemp fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Existing works with natural fibers are relatively different and commonly use a fossil‐based matrix. Examples include fossil‐based epoxy composites with woven fiber mats, 28 delignified wood pulp fibers, 29 or alkali and silane‐treated hemp fibers 30 . These fibers often involve special processing and are not sourced as waste.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing works with natural fibers are relatively different and commonly use a fossil‐based matrix. Examples include fossil‐based epoxy composites with woven fiber mats, 28 delignified wood pulp fibers, 29 or alkali and silane‐treated hemp fibers 30 . These fibers often involve special processing and are not sourced as waste.…”
Section: Resultsmentioning
confidence: 99%
“…Examples include fossil-based epoxy composites with woven fiber mats, 28 delignified wood pulp fibers, 29 or alkali and silane-treated hemp fibers. 30 These fibers often involve special processing and are not sourced as waste. As a result of the excellent fiber parameters, they can achieve a Young's modulus in the range of 2-6 GPa and a tensile strength of around 30-100 MPa.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…It is due to improved fiber-matrix interfacial characteristics resulting from chemical treatment. 28 The addition of flame retardants to composites resulted in an increased burning time and lowered the burning rate. Increased loading of flameretardant fillers in composites delayed the flame propagation and resulted in char formation.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…Sv et al [40] investigated the influence of 5% NaOH at various soaking times (15,30,45,60, and 75 min) on Ziziphus nummulania fibers. They reported that 60 min was the optimal soaking time.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] The easy availability, biodegradability, minimum cost, low density, high specific strength, and non‐toxicity are some attractive features of natural fiber. [ 6–8 ] In recent years, natural fibers like luffa, [ 9 ] pistachio shell particles, [ 10 ] rice straw, [ 11 ] sea purslane, [ 12 ] groundnut shell powder, [ 13 ] kenaf, [ 14 ] hemp, [ 15 ] jute, [ 16 ] limonia acidissima shell powder, [ 17 ] and tamarind powder [ 18 ] have proved their potential as a reinforcement material in different polymer matrices as reported by the researchers. Despite several attractive properties, the natural fibers are not free from a specific defect, that is, poor compatibility between fiber and matrix.…”
Section: Introductionmentioning
confidence: 99%